Ethnomedicine for diarrhoea and dysentery by the tribes of Srikakulam district, Andhra Pradesh - B.V.A. Ramarao Naidu; T.V.V. Seetharami Reddi (Journal of Traditional and Folk Practices (JTFP), 2016)
The paper deals with 65 species of plants covering 58 genera under 43 families used by the tribes of Srikakulam district for curing diarrhoea and dysentery. Family-wise analysis showed the dominance of Rutaceae and Rubiaceae with 4 species each followed by Fabaceae, Caesalpiniaceae, Mimosaceae, Apocynaceae, Ebenaceae each with 3 species and others. Habit-wise analysis showed the dominance of trees with 31 species followed by herbs (19), shrubs (11) and others. Leaf is used in maximum practices (16) followed by stem bark (15), root (10) and others. Thirty two plants are exclusively used for curing diarrhoea followed by 24 for dysentery and 9 for both. Information on Diospyros chloroxylon and 15 practices were found to be new or less known.